تاريخ الكويت: مما غاب عن ذاكرة المؤرخ - Al-Awadi, Hesham (2025)
The book sheds light on groups that have been absent from the historian’s memory, despite their important role in Kuwait’s history. It examines two categories: first, Kuwaitis who lived outside the city wall—among them Bedouins and the inhabitants of villages and islands; and second, those who lived inside the wall but did not receive attention from traditional historians. The desert was not merely a barren expanse, as is often assumed; rather, it played a major role in saving the city from collapse during its crisis between the decline of the pearl trade and the rise of oil. The inhabitants of the desert also played a central role in the founding of the state and the protection of its borders. As for the villages, they were not “backyards” for leisure, but active centers that contributed to pivotal events, such as the Battle of Jahra in 1920. The islands, too, were not isolated , but played a role in shaping Kuwait’s final borders. Within the heart of the city lived groups that were rarely highlighted: Arabs coming from Persia, slaves, non-Muslims, the poor, the sick, and all those absent from the dominant narrative. The book does not present an alternative narrative, but rather broadens the lens through which we read the past. It emphasizes that the history of Kuwait was not a single voice, but multiple voices—voices that historians must listen to and amplify, regardless of their number, status, or place of residence.